Incidence, outcome, and prognostic factors of prolonged mechanical ventilation among children in Chinese mainland: a multi-center survey - Zhengzheng Zhang; Xiaodi Cai; Meixiu Ming; Li Huang; Chengjun Liu; Hong Ren; Dong Qu; Hengmiao Gao; Yibing Cheng; Furong Zhang; Zihao Yang; Wei Xu; et al. (Frontiers Media S.A., 2024)
ObjectiveTo evaluate the incidence, outcome, and prognostic factors of prolonged mechanical ventilation (PMV) in children in Mainland China.MethodsA prospective study was conducted in 11 pediatric intensive care units (PICUs) from May 1, 2021, to April 30, 2022. All pediatric patients on mechanical ventilation meeting the criteria for PMV were included in the study.ResultsOut of 5,292 patients receiving mechanical ventilation, 278 children met the criteria for PMV (5.3%). After excluding case with incomplete data or lost to follow-up, the study included 250 patients. Among them, 115 were successfully weaned from mechanical ventilation, 90 died, and 45 were still on mechanical ventilation. The 6-month survival rate was 64%. The primary associated conditions of PMV were lower airway diseases (36%), central nervous system diseases (32%), and neuromuscular diseases (14%). The stepwise multiple logistic regression analysis indicated that the utilization of vasoactive agents and an elevated pediatric logistic organ dysfunction-2 (PELOD-2) score on the day of PMV diagnosis were significantly associated with an increased of PMV death. Specifically, the odds ratio (OR) for vasoactive agent use was 2.86; (95% CI: 0.15-0.84; P = 0.018), and for the PELOD-2 score, it was 1.37; 95% CI: 1.17-1.61; P < .001). Conversely, early rehabilitation intervention was negatively associated with the risk of PMV death (OR = 0.45; 95% CI: 0.22-0.93; P = .032). Furthermore, the tracheotomy timing emerged as an independent predictor of failure to wean from PMV, with an OR of 1.08, (95% CI: 1.01-1.16; P = .030).ConclusionsThe study revealed a 5.3% incidence of PMV in children requiring mechanical ventilation in China. The use of vasoactive agents and a higher PELOD-2 score at PMV diagnosis were significantly associated with an increased risk of PMV death, whereas early rehabilitation intervention was identified as crucial for improving patient outcomes. The timing of tracheostomy was identified as a high-risk factor for failure to wean from mechanical ventilation.